Domínios de Dedekind como inserção de anéis de valorizações discretas - Mello, Cristiane de (2006)
In this work we present the Dedekind domains as the intersection of discrete valuation rings of its field of fractions, of a family of valuations with the strong approximation property, we show the equivalence of this definition with the usual definition and that the a property is preserved in separable extensions of fields.